Genetic compensation response could exist in colorectal cancer: UPF3A upregulates the oncogenic homologue gene SRSF3 expression corresponding to SRSF6 to promote colorectal cancer metastasis. Issue 4 (2nd March 2023) - Xu, Weimin; Ou, Weijun; Feng, Yuan; Xu, Qingru; Yang, Yili; Cui, Long; Du, Peng
Abstract: Background: Genetic compensation response (GCR) is a mechanism that maintains the robustness of functional genes, which has been recently identified. Whether GCR exists in tumors and its effects on tumor progression remains unknown. Methods: Whole exome sequencing was performed to identify premature termination codon (PTC) gene mutations in colorectal cancer (CRC) tissues. RNA sequencing, Cancer Cell Line Encyclopedia database analysis, and high‐throughput output of homologous genes using the Ensemble genome database were performed to further identify homologous genes of target PTC gene mutations. Results: Serine and arginine‐rich splicing factor 3 (SRSF3) increased the invasion ability in CRC cells and could be the target gene of up‐frameshift 3A (UPF3A). The deletion of the 660th base A in the coding sequence region of SRSF6 caused a frameshift mutation of serine at position 220 (s220fs), which contributed to a PTC UAA termination of translation in HCT116 cells. We further found that SRSF3 was the only homologue of SRSF6 with a frameshift mutation. The transfection of s220fs of SRSF6 into HCT116 cells led to upregulation of its corresponding oncogenic homologue gene SRSF3 expression to promote CRC metastasis. SRSF3 was highly expressed in CRC liver metastases and was positively correlated with UPF3A expression and contributed to poor prognosis. Conclusion: GCR may exist in CRC and exert effects on the progression of CRC. Targeted inhibition of UPF3A could reduce the GCR effects and suppress the expression of oncogenic homologue genes corresponding to PTC mutations, indicating a novel therapeutic strategy for treatment of CRC metastasis.